2020
DOI: 10.1039/d0fo01394c
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation ofLactobacillus acidophilusNCDC 016 cells by spray drying: characterization, survival afterin vitrodigestion, and storage stability

Abstract: L. acidophilus was encapsulated with maltodextrin and different concentrations of gum arabic by spray drying technology. Encapsulated cells have shown better viability under simulated gastrointestinal conditions compared to free cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 47 publications
6
46
0
Order By: Relevance
“…This distribution of sizes was confirmed by the image analysis, which allowed identify capsules diameters from 1 to 150 µm. These results are similar to those reported by Arepally et al (2020b), who obtained a probiotic powder with smaller size than the droplets formed by encapsulating agents (arabic gum, maltodextrin and combination of both) in emulsion. The decrease in size of the droplets generated in the emulsion is mainly due to the evaporation of water during the drying process.…”
Section: Morphological Analysis Of the Microcapsules Spray-driedsupporting
confidence: 91%
See 3 more Smart Citations
“…This distribution of sizes was confirmed by the image analysis, which allowed identify capsules diameters from 1 to 150 µm. These results are similar to those reported by Arepally et al (2020b), who obtained a probiotic powder with smaller size than the droplets formed by encapsulating agents (arabic gum, maltodextrin and combination of both) in emulsion. The decrease in size of the droplets generated in the emulsion is mainly due to the evaporation of water during the drying process.…”
Section: Morphological Analysis Of the Microcapsules Spray-driedsupporting
confidence: 91%
“…This viability was significant higher (p<0.05) than those observed at inlet temperatures of 150 and 190 ºC. This significant increase of viability at 170 ºC inlet temperature can be attributed to the moisture content of dry capsules since it has been observed that a moisture content between 4 and 7% generates a greater stability of dry capsules and greater viability of the encapsulated microorganism (Arepally et al, 2020b). Based on this, the highest viability observed in the capsules spray-dried at 170 ºC inlet temperature can be explained as a function of their moisture content (6.95% db), ensuring high stability and protection of encapsulated probiotic.…”
Section: Viability Of Encapsulated Lp-lbc and Physicochemical Properties Of Dry Microcapsulesmentioning
confidence: 75%
See 2 more Smart Citations
“…It was proved earlier that in low pH conditions most of the un-encapsulated cells were damaged and destroyed (Shi et al., 2013). Thus the shielding effect of carrier materials makes it a promising encapsulation agent by protecting the cells against bile and gastric juices (Arepally et al., 2020; Zhang et al., 2018). This increased survival may also be correlated with the synergistic activity of FMM serving as a supplement to increase the viability of strains under low pH environment.…”
Section: Resultsmentioning
confidence: 99%